METHOTREXATE-ASSOCIATED STEVENS-JOHNSON SYNDROME AND TOXIC EPIDERMAL NECROLYSIS: TWO CASE REPORTS - Yakup Unsal; Muhammed Murati; Guler Delibalta; Serdar Bedii Omay; Vildan Yazici; Nedim Polat (Hematology, Transfusion and Cell Therapy)
Objective: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are rare but severe mucocutaneous diseases. These conditions are mostly drug-induced and have high mortality rates. They are primarily characterized by skin and mucosal involvement. In addition to supportive treatments, plasmapheresis and immunosuppressive drugs are used in treatment. We present our experience with 2 cases of SJS/TEN that developed after high-dose Methotrexate use in the treatment of two different hematological malignancies. Case report 1: A 58-year-old male was diagnosed with Primary Central Nervous System (CNS) Lymphoma in August 2024. The patient started on MATRIX (Methotrexate 3000 mg/m²/day, Cytarabine 1000 mg/m²/day, Rituximab 375 mg/m²/day) therapy. On September 2, 2024, the first cycle of treatment was administered. On the 8th day, erythematous rashes appeared on the palms and soles. The patient was consulted with dermatology and received local treatment for a suspected drug reaction. The lesions resolved. During the second cycle of MATRIX therapy on September 30, 2024, the patient received four doses of intrathecal Methotrexate 12 mg and Cytarabine 100 mg by October 3, 2024. On the fourth day of treatment, the creatinine level rose to 3.05 mg/dL (baseline 0.9 mg/dL). Suspecting toxic nephropathy, hydration therapy was initiated under nephrology consultation. On the 10th day of treatment, the patient developed a fever above 38°C, accompanied by erythematous lesions on the skin, particularly in the oral mucosa. Following the recommendation of the Infectious Diseases Department, treatment with Cefoperazone/Sulbactam and Micafungin was initiated. During the same period, the patient developed diarrhea (6‒8 times per day) and was given symptomatic treatment. On the 13th day of treatment, as skin rashes increased, Prednisolone (1 mg/kg) was initiated. However, the skin lesions continued to progress. On the 15th day of treatment, with a creatinine level of 1.8 mg/dL, the patient developed absolute neutropenia. Filgrastim (G-CSF) therapy was started. The patient was consulted with the Dermatology Department due to the skin lesions. Pale erythema on the skin and erythematous patches with targetoid vesicles on the extremities were observed. The body surface area involvement was estimated to be approximately 10%‒30%. A skin biopsy was performed, and the findings were reported as Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis (SJS/TEN). Based on the current findings, the patient was diagnosed with SJS/TEN Overlap Syndrome, and pulse Prednisolone 500 mg was initiated for 3 days. Due to elevated acute phase reactants and absolute neutropenia, the Infectious Diseases Department recommended discontinuing Cefoperazone & Sulbactam treatment. The patient was then started on Meropenem and Daptomycin. On the 23rd day of treatment, as the skin lesions continued to progress, Cyclosporine A therapy was considered. However, due to ongoing Acute Renal Failure, Tacrolimus infusion was initiated instead. Concurrently, plasmapheresis (1:1) was performed. On the 25th day of treatment, the patient remained in absolute neutropenia (neutrophil count: 0), and IVIG (0.4 g/kg/day) was started. On the 26th day, the patient developed desaturation and was transferred to the intensive care unit, where elective intubation was performed. The patient was connected to a mechanical ventilator, but unfortunately, on the 27th day of treatment, the patient died due to multiorgan failure. Case report 2: A 34-year-old female patient was diagnosed with Acute Lymphoblastic Leukemia (B-ALL) in December 2024. The patient, who was Philadelphia chromosome-negative, received the first cycle of Hyper-CVAD therapy (Cyclophosphamide 2 × 300 mg/m²/day for 3 days, Vincristine 2 mg/day, Adriamycin 50 mg/m²/day, Decort 40 mg/day for 4 days). Remission was achieved, and a total of 3 doses of intrathecal Methotrexate 12 mg and Cytarabine 100 mg were administered. On January 6, 2025, the second cycle of Hyper-CVAD therapy (Methotrexate 1000 mg/m²/day, Cytarabine 2 × 3000 mg/m²/day for 2 days, Prednisolone 2 × 25 mg/m²/day for 3 days) was initiated. On the 4th day of treatment, the creatinine level was found to be 3.96 mg/dL. At the beginning of the treatment, the patient's creatinine level was 0.77 mg/dL. The patient was consulted with Nephrology, and acute renal failure due to toxic nephropathy was considered. Emergency dialysis was not deemed necessary. Hydration and symptomatic treatment were recommended for follow-up. On the 6th day of treatment, the patient developed a fever above 38°C. Considering the presence of neutropenia, Cefoperazone & Sulbactam treatment was initiated upon the recommendation of the Infectious Diseases Department. On the 8th day of treatment, the patient experienced a sudden speech disorder accompanied by dizziness. Brain CT and Diffusion MRI showed no signs of bleeding or ischemia. No findings suggestive of ALL involvement were observed in the contrast-enhanced Brain MRI. The CSF cytology was normal. Due to suspicion of ALL involvement, a dose of intrathecal Methotrexate 12 mg and Cytarabine 100 mg was administered. Neurology consultation suggested the possibility of an atypical epileptic seizure. Antiepileptic treatment was initiated. As the creatinine level decreased to 1.96 mg/dL and no other pathological condition explaining the existing neurological findings was identified, CNS involvement of ALL was considered, and Radiotherapy (RT) was planned. Consultation with Radiation Oncology led to the initiation of CNS radiotherapy, with a total of 4 RT sessions administered. On the 10th day of treatment, Filgrastim (G-CSF) was started for the patient who was in absolute neutropenia. On the 11th day of treatment, erythematous rashes developed on the extremities and genital area, along with vesicular rash lesions on the back. The patient was consulted with Dermatology, and considering the possibility of Toxic Epidermal Necrolysis (TEN), a skin biopsy was performed. The biopsy result confirmed TEN. The patient was started on pulse prednisolone 1000 mg for 3 days. Along with steroids, plasmapheresis (1:1) was administered. On the 13th day of treatment, the patient developed a fever over 38°C, and based on the recommendations of the Infectious Diseases Department, the cefoperazone & sulbactam treatment was discontinued. As the creatinine level decreased to 1.1 mg/dL, Colistin and Imipenem were started. The patient's total bilirubin level increased to 7.68 mg/dL (with a predominance of direct bilirubin) compared to the previous day's total bilirubin level of 1.96 mg/dL. Due to the lack of significant improvement in skin lesions, a second session of plasmapheresis (1:1) was performed on the 15th day of treatment. On the 16th day of treatment, the patient's total bilirubin level increased to 17 mg/dL. Concurrently, the patient developed hypernatremia (Na: 166 mmoL/L), and emergency hemodialysis was planned upon the recommendation of Nephrology. A 2-hour hemodialysis session was performed. At the end of dialysis, the patient experienced respiratory arrest. The patient was electively intubated and transferred to the intensive care unit. Despite high-dose positive inotropic support, the patient developed cardiac arrest and died on the 17th day of treatment due to multiorgan failure. Conclusion: Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are clinical conditions with high morbidity and mortality, often triggered by medications. The most common culprits include sulfonamides, anticonvulsants, Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), and beta-lactam antibiotics. Clinically, SJS/TEN presents with fever, along with skin and mucosal membrane lesions. When vesicular lesions cover less than 10% of the body surface, it is considered SJS; when over 30%, it is classified as TEN, and if between 10%‒30%, it is considered SJS/TEN overlap syndrome. In our first case, the involvement was between 10%‒30%, leading to the diagnosis of SJS/TEN Overlap Syndrome. In the second case, as the lesions involved more than 30% of the body surface, the diagnosis of TEN was made. Methotrexate, widely used in various diseases, is associated with side effects such as nephrotoxicity, hepatotoxicity, bone marrow toxicity, and mucositis. Dermatological side effects, including urticaria, maculopapular rashes, mucositis, erythema, TEN, SJS, and psoriatic rashes, have also been reported. Methotrexate-induced SJS/TEN in the literature is attributed to direct cellular toxicity, hypersensitivity, or drug interactions, such as with NSAIDs. There is ongoing debate about whether the resulting epidermal necrolysis is due to dose-dependent toxicity or an allergic reaction. In our two cases, high-dose methotrexate was administered due to primary hematologic malignancies. Adequate doses of folic acid were provided 24 hours after Methotrexate administration. Both cases initially developed nephrotoxicity following methotrexate use, subsequently leading to skin involvement. Early treatment strategies, including steroids, Intravenous Immunoglobulin (IVIG), and supportive care as recommended in the literature, were implemented. However, both patients developed complications related to absolute neutropenia due to high-dose chemotherapy combined with methotrexate. SCORTEN scores were determined to be very high, at 5 or above. Unfortunately, both of our cases were lost due to the development of multi-organ failure. In conclusion, patients undergoing high-dose methotrexate therapy require close monitoring for nephrotoxicity and skin reactions to mitigate potentially fatal outcomes.